 Proposition 5

h

f

i

0

F

(Src

f

)

= 0

F

(Dst

f

)

for every funcoid

f

.

Proof

Y 6≍ h

f

i

0

F

(Src

f

)

0

F

(Src

f

)

6≍

f

1

Y ⇔

0

⇔ Y 6≍

0

F

(Dst

f

)

. Thus

h

f

i

0

F

(Src

f

)

= 0

F

(Dst

f

)

by separability of filter objects.

Proposition 6

h

f

i

(

I ∪ J

) =

h

f

i I ∪ h

f

i J

for every funcoid

f

and

I

,

J ∈

F

(Src

f

)

.

Proof

h

f

i

(

I ∪ J

) =

{Y ∈

F

| Y 6≍ h

f

i

(

I ∪ J

)

}

=

Y ∈

F

| I ∪ J 6≍

f

1

Y

=

(by corollary 10 in )

Y ∈

F

| I 6≍

f

1

Y ∨ J 6≍

f

1

Y

=

{Y ∈

F

| Y 6≍ h

f

i I ∨ Y 6≍ h

f

i J }

=

{Y ∈

F

| Y 6≍ h

f

i I ∪ h

f

i J }

=

(

h

f

i I ∪ h

f

i J

)

.

Thus

h

f

i

(

I ∪ J

) =

h

f

i I ∪ h

f

i J

because

F

(Dst

f

) is separable.

Proposition 7

For every

f

FCD

(

A

;

B

)

for every small sets

A

and

B

we

have:

1.

K

[

f

]

I ∪ J ⇔ K

[

f

]

I ∨ K

[

f

]

J

for every

I

,

J ∈

F

(

B

)

,

K ∈

F

(

A

)

.

2.

I ∪ J

[

f

]

K ⇔ I

[

f

]

K ∨ J

[

f

]

K

for every

I

,

J ∈

F

(

A

)

,

K ∈

F

(

B

)

.

Proof

1.

K

[

f

]

I ∪J ⇔

(

I ∪ J

)

∩h

f

i K 6

= 0

F

(

B

)

(

I ∩ h

f

i K

)

(

J ∩ h

f

i K

)

6

=

0

F

(

B

)

⇔ I ∩ h

f

i K 6

= 0

F

(

B

)

∨ J ∩ h

f

i K 6

= 0

F

(

B

)

⇔ K

[

f

]

I ∨ K

[

f

]

J

.

2. Similar.

3.2.1

Composition of funcoids

Definition 20

Funcoids

f

and

g

are

composable

when

Dst

f

= Src

g

.

Definition 21

Composition

of composable funcoids is defined by the formula

(

B

;

C

;

α

2

;

β

2

)

(

A

;

B

;

α

1

;

β

1

) = (

A

;

C

;

α

2

α

1

;

β

1

β

2

)

.

Proposition 8

If

f

,

g

are composable funcoids then

g

f

is a funcoid.

Proof

Let

f

= (

A

;

B

;

α

1

;

β

1

),

g

= (

B

;

C

;

α

2

;

β

2

). For every

X ∈

F

(

A

),

Y ∈

F

(

C

) we have

Y 6≍

(

α

2

α

1

)

X ⇔ Y 6≍

α

2

α

1

X ⇔

α

1

X 6≍

β

2

Y ⇔ X 6≍

β

1

β

2

Y ⇔ X 6≍

(

β

1

β

2

)

Y

.

11